Development of Inventory Information System Using Enterprise Architecture Planning Method - Muhammad Sobri; Poppy Indriani; Mohamad Taha Ijab; Isnawijayani Isnawijayani; Marlindawati Marlindawati (JOIV : International Journal on Informatics Visualization, 2019)
Universitas Bina Darma is a university that has a vision to become an international standard university driven by innovations in Information and Communication Technology (ICT). The aim of this research is to support the vision of Universitas Bina Darma by creating an inventory information system for the university-wide implementation. The research uses Enterprise Architecture Planning (EAP) which defines the data architecture, application architecture, technology architecture, and its implementation. EAP consists of four levels, where by the top level is planning initiation, the second level consists of two stages namely business modeling, and current systems and technology, the third level consists of three stages of data architecture, application architecture and technology architecture. Lastly, the bottom level is implementation or migration plans. The results of this research is in the form of the Inventory Information Systems that has several menus, among others: procurement menu, maintenance menu, move transfer menu, space menu, loan space menu, asset menu and request menu. This Inventory Information System facilitates the faster processing of inventory data so as to produce quality report Â that is timely available when needed by the leadership, as well as facilitates the supervision of existing inventory.